Influences of Proximate Determinates on Fertility Among Urban and Rural Women in Bangladesh - Hasan, Muhammad Mahmudul; Islam, Mirajul; Sakib, Md Saifullah; Haq, Md Iqramul (Dhaka University Journal of Science, 2018)
Bangladesh has met a lot of challenges in recent decades. The remarkable decline in fertility is one of the major challenges faced by this country. The rate of fertility in rural areas is still higher than urban areas. The proximate determinants of fertility which influence fertility directly are analyzed in this study for urban and rural areas separately as well as the study quantify the decomposition of the differences in total fertility rate (TFR) in residence during 1993-94 to 2014. The effectiveness of contraceptive use is found to be the most important factor for declining fertility. The result revealed that the index of contraception shows a declining trend, indicating an increasingly inhibiting effect on fertility in both urban and rural areas of Bangladesh. The inhibition effect of postpartum infecundability decreases with increase in urbanization. The decomposition analysis shows that fertility decline has been occurred due to delay marriage, increase of contraception practice, shortening of postpartum infecundability period, increase proportion in induced abortion and the interaction factor. Dhaka Univ. J. Sci. 66(1): 49-54, 2018 (January)